150 years of the Trades Union Congress – reflections on the past and challenges for the future. Issue 2 (11th February 2019) - Nowak, Paul; Hodder, Andy
Abstract : Purpose: The purpose of this paper is to look back on 150 years of the Trades Union Congress (TUC) and reflect on the recent challenges to organised labour. Design/methodology/approach: Places unions in their current context and discusses how they have responded to the challenge of declining membership. Findings: With declining membership levels and the lack of a "silver bullet" solution, unions continue to face many challenges, although there is some light at the end of the organising tunnel. Originality/value: This paper introduces the special issue which reflects on 150 years of the TUC.